Usage of selective local crops for goat feeding regime to increase milk and meat yield - Mohd Amin, Mohd Hishammfariz; Mat Yusof, Afzan (2018)
The success of goat management in terms of milk and meat production relied on the types of feeding materials. The use of imported crops is more common, leading to the stagnation and underutilization in the availability of local crops. In this study, local crops feeding regime or new feeding regime was formulated to compare with the existence imported crops feeding regime or old feeding regime used by the goat farmer. Goats’ body weight gain and daily milk yield were measured as indicators of the feed formulation efficacy and goats’ performance. A total of twenty adult female Saneen goats with body weight approximately 30-35 kg were fed with two different feed formulations for six months. The goats were fed with imported feeding regime (Diet 1) for the first three months and continued with local crops feeding regime (Diet 2) for the next three months. Body weight and daily milk production was measured on Day 7, 14, 21 and 28 of every month. The goats fed with Diet 2 showed higher body weight gain and milk production than Diet 1. The results suggested that the implementation of feed formulation using local crops is recommended as it increases goats’ milk and meat production.